Contemporary Traditions and Challenges: Tafsir Maudhu’I’s Study of Islam and Fundamentalism - Nur Zen Hasanah; Rizki Alfi; Ria Rifkiah; Asep Abdul Muhyi (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2024)
Islam and fundamentalism have become significant subjects in contemporary studies of religion and politics. The presence of fundamentalism in the context of Islam poses complex challenges, particularly in managing the relationship between tradition and contemporary realities. This research employs descriptive and thematic content analysis methods to analyze the phenomenon of Islamic fundamentalism, exploring its origins, characteristics, and impacts in social, political, and cultural contexts. Through a descriptive approach, this research provides a comprehensive overview of the phenomenon of Islamic fundamentalism from historical, doctrinal, and practical perspectives. Thematic content analysis allows for an understanding of interpretations and applications of Islamic doctrines that underpin fundamentalist movements. The findings highlight the complexity of the relationship between the rich tradition of Islam and rapidly changing contemporary contexts. While fundamentalism often claims to uphold the